Biostatistical analysis for dentistry : a guide to SPSS - Mohd Ibrahim, Mohamad Shafiq; Che Musa, Muhd Firdaus; Sayed Kamar, Syarifah Haizan; Wan Ahmad, Wan Muhamad Amir (IIUM Press, 2025)
Welcome to Biostatistical Analysis for Dentistry: A Guide to SPSS. This book is more than just a manual—it is a comprehensive resource designed to equip dental students, researchers, and practitioners with a solid understanding of biostatistics and its practical applications in dentistry. Selecting the appropriate statistical test is a critical step in data analysis, as the correct test enables accurate interpretation and sound conclusions, while the wrong choice can lead to misinterpretation and flawed results. This guide provides a step-by-step walkthrough, beginning with file creation and data entry using IBM SPSS Statistics version 28, followed by descriptive statistics and data visualisation. It then covers inferential statistics, including parametric tests (one-sample t-test, independent sample t-test, paired t-test, and one-way ANOVA), nonparametric tests (one-sample Wilcoxon signed-rank test, Mann-Whitney U test, Wilcoxon signed-rank test, and Kruskal-Wallis test), crosstabulation analyses (Chi-Square test, Fisher’s exact test, and McNemar’s test), as well as correlation and simple linear regression. Each section features practical examples with real datasets, enabling users to build confidence through hands-on application. We hope this book serves as a valuable companion for both beginners and experienced researchers seeking to refine their analytical skills. May it inspire clarity, confidence, and rigour in your statistical work, and contribute meaningfully to the advancement of dental research and practice. Thank you for choosing this book—we wish you continued success in your academic and professional journey.